Assessment of propulsive pin force and oar angle time-series using functional data analysis in on-water rowing - Warmenhoven, J.; Cobley, S.; Draper, C.; Harrison, A.; Bargary, N.; Smith, R. (Scandinavian Journal of Medicine & Science in Sports, 2017)
The graphical presentation of the propulsive force applied at the pin plotted relative to the horizontal angle of the oar has been used practically in on-water rowing for the qualitative assessment of skill. How the pattern is related to performance variables has not been well identified, particularly for highly trained sculling athletes. Bivariate functional principal components analysis (bfPCA) was used on force-angle data to identify the main modes of variance in curves representing twenty seven female rowers of different competition levels (national and international level), rowing at 32 strokes per minute in a single scull boat. Discriminant function analysis showed moderate classification of rowers using force-angle graphs across both sides of the boat, with rate of force development identified as a potentially important characteristic for international rowers. Additionally for the bow-side, spending less time in the first half of the drive phase was also identified as an important feature for international rowers. Multiple linear regression of scores from the bfPCAs showed that a more pronounced front peaked profile was associated with a higher average boat velocity. The results of this demonstrate that different characteristics of the force-angle graph may be associated with different metrics of performance.